Molecular and Synaptic Bases of CDKL5 Disorder - Zhu, Yong‐Chuan; Xiong, Zhi‐Qi (Developmental neurobiology (Hoboken, N.J.), 2019)
The X‐linked gene cyclin‐dependent kinase‐like 5 (CDKL5) encodes a serine/threonine kinase abundantly expressed in the brain. Mutations in CDKL5 have been associated with neurodevelopmental disorders characterized by early‐onset epileptic encephalopathy and severe intellectual disability, suggesting that CDKL5 plays important roles in brain development and function. Recent studies using cultured neurons, knockout mice, and human iPSC‐derived neurons have demonstrated that CDKL5 regulates axon outgrowth, dendritic morphogenesis, and synapse formation. The role of CDKL5 in maintaining synaptic function in the mature brain has also begun to emerge. Moreover, mouse models that are deficient for CDKL5 recapitulate some of the key clinical phenotypes in human patients. Here we review these findings related to the function of CDKL5 in the brain and discuss the underlying molecular and cellular mechanisms.